Large scale electricity storage technology options for smart grid - Salkuti, Surender Reddy (International Journal of Engineering and Technology, 2018)
This paper aims to establish a comparative analysis between various storage techniques available and to evaluate their current impact as well as potential to be employed more effectively in the future. This paper presents the classification of each storage technique on the basis of features, cost, location, mathematical modelling, advantages and disadvantages. This paper shows the energy storage devices behavior to effectively improve the renewable energy sources connected to the utility grid. The paper also identifies the different storage techniques that can be implemented in to a smart grid and a cost benefit analysis of the different storage techniques. The paper exhaustively reviews the functionality of a major sector of smart grid and energy storage. From this paper, it can be observed that the use of energy storage technologies will increase the supply, and balances the demand for energy.